Afrocentric frameworks in recreation and leisure research: a perspective article - Sakala, Michael (Frontiers in Sports and Active Living, 2024)
This perspective article re-imagines and proposes key Afrocentric frameworks that can contribute towards animating the recreation and leisure discourse in Africa. The article foregrounds Afrocentricity, Sankofa, African Social Ontogenesis and Ubuntu as pertinent lenses through which recreation and leisure phenomena can be explored to respond to African realities. The article analytically draws on relevant scholarship to describe and interpretively glean implications for recreation and leisure research. The article's contribution to the discourse lies in its call for a rethink on how recreation and leisure research should engage with African realities.